Kamila Shamsie’s Kartography and the Itinerary of Cultural Identity: Mapping Traumatic Experience within the “Canker” of History Keep moving, it’s not our destination, yet…♦ Faiz Ahmed Faiz - David Waterman (Sillages Critiques)
In Kamila Shamsie's 2002 novel, the 1971 Pakistan civil war becomes the traumatic experience which is everyone's psychological benchmark, even for those not yet born -- the young protagonists wonder “Is it shame at losing the war, or guilt about what we did to try to win that mutes us?”, a collective aphasia which is symptomatic of these characters' inter-generational traumatic experience. Borrowing from Moira Fradinger's concept of binding violence, we will see how a structure of enmity was created, as a means of defining an internal enemy -- Pakistanis become Bangladeshis -- as a means of re-drawing the map of Pakistan, with the goal of erasing certain elements of the past, even going so far as to imply what Philip Gourevitch calls “socially constructive genocide.”